Overstock Improvement by Combining Forecasting, EOQ, and ROP - Hasbullah Hasbullah; Yadi Santoso (Jurnal PASTI (Penelitian dan Aplikasi Sistem dan Teknik Industri), 2020)
Optimum stock inventory level is an essential factor in inefficient production. Overstock is an obstacle to achieving optimum cost. The purpose of this paper is to provide solutions in overstock in the electronic spare parts industry by comparing the various approaches Forecasting, EOQ, ROP with DDMRP to get the best model to obtain the inventory level Optimally. The Reset is done on the material Copper wire 0, 14mm as the primary material, which is the most expensive material and widely used in production activities. The results of this study showed that the method of DDMRP could decrease the average amount of the supply of Copper wire 0, 14mm per month from 2779 kg to 1499 kg.